Developing Research Skills among Undergraduate Students by Student-centered Active Learning Approaches - Rizwana Wahid; Shanjida Halim; Tanzina Halim (Kurdish Studies, 2023)
Developing research skills among undergraduate students is a very challenging task for teachers. Studying research skills/the course on research methods, students also find it daunting, especially undergraduate students. Students are novices in this course, and they do not see the relevance and value of research skills. As a result, they find it boring and not useful for their professional life and feel uninterested and unmotivated to study this course. Teachers have a double responsibility: to clarify the basics of research skills and involve the learners in research with interest. The study intends to determine if research skills are developed through student-centered active learning approaches that may motivate students to perform better. For this purpose, data was collected from 60 participants (15 teachers, and 45 students). Then, the data was coded in the descriptive analysis by using SPSS (Statistical Package for the Social Sciences-version 26). These teachers are either teaching this course or have already taught it and students are either studying or have already studied it. The research findings revealed the necessity of enhancing understanding through motivation and involving students through activity-based and student-centered approaches. Further, the study recommends that teachers adapt teaching materials according to the nature of this course and the students' needs (their prior knowledge, context, interest, etc.).